PENDIDIKAN AGAMA: MENJAWAB TANTANGAN MODERNISASI - Abdullah, Jihan (State Institute of Islamic Studies (IAIN) Palu, 2006)
Modernization often creates a paradigm and new values. Therefore, people who envlove in it including learners are faced with two facts; whether they are resistennt when interacting with it or accept it with all its consequences. Based on this, we need supreme morality to prevent or at least to descrease secularism- in many occations- is produced by modernization.Within this context, Islamic education which has for long time been taught to students at schools, seems less able to-in many cases- save students’ morality without disregarding external factors, of course. So, what’s actually wrong with our Islamic education. Kata Kunci: Modernisasi, pendidikan agama, perubahan kurikulum